Two dimensional elastic deformations of functionally graded coated plates with clamped edges - Zaki M.; Tarlochan F.; Ramesh S. (2023)
Over the years new coating design and technology for structures have received much attention mainly due to the demand for longer life span and durability. Conventional coating general consists of few homogeneous layers being deposited on the parent material or substrate. These layers are very vulnerable to cracking followed by de-bonding due to mismatch thermo-mechanical property. To avoid such coating failures, functionally graded material (FGM) is proposed in the coating design. Hence, this study analyzes FGM plates subjected to transverse load with clamped edges. Three configurations were considered. The first involves a two-layer plate in which a homogeneous coating layer was coated on a homogeneous substrate. The second involves a two layer system with the first layer as a FGM coating followed by the homogeneous substrate and the final configuration was a three layer system. The top and bottom layers are homogenous coating and substrates respectively, and the interlayer is composed of FGM. The Young's modulus of FGM plates is assumed to vary in the thickness direction based on the sigmoid functions and the Poisson's ratio remain constant throughout the FGM plate. The analysis was carried out in the context of two-dimensional elasticity theory and the method of superposition was used to find a series solution. The deflections, strains, and stresses were evaluated and the differences between the elastic behaviors of all three design configurations were investigated. 2012 Elsevier Ltd. All rights reserved.